Subthreshold laser treatment for retinal arterial macroaneurysm associated with exudative maculopathy - Bhat, Parvez Ahmad (Oman J Ophthalmol, 2019)
In this article, we present a case of retinal arterial macroaneurysm (RAM) complicating into exudative maculopathy who was successfully treated with subthreshold laser treatment (STLT). A 45-year-old Indian female was referred to our institution with diminution of vision in her left eye for 1 month with best-corrected visual acuity (BCVA) of counting fingers at 2 m in the left eye. A dilated fundus examination of the left eye revealed deposition of lipid exudates in the macular area and a reddish round vascular lesion superior to macula around two disc diameters from the center of fovea. Optical coherence tomography (OCT) showed serous neurosensory detachment in the macular area in the left eye. Fundus fluorescein angiography showed leakage at the site of vascular lesion in the arterial phase of angiogram. Laser treatment using subthreshold laser parameters was done with three mirror contact lens at the site of vascular lesion. Over the next 12-month follow-up, her BCVA as well as OCT picture improved gradually, and at the last follow up, her BCVA was 20/30 in the left eye with complete resolution of subretinal fluid as detected by OCT. STLT offers promising results in the treatment of symptomatic RAM without causing any complications.